An Amorphous n‐Type Conjugated Polymer with an Ultra‐Rigid Planar Backbone. (2nd December 2022) - Cao, Xu; Li, Hongxiang; Hu, Junli; Tian, Hongkun; Han, Yanchun; Meng, Bin; Liu, Jun; Wang, Lixiang
Abstract: High charge carrier mobility polymer semiconductors are always semi‐crystalline. Amorphous conjugated polymers represent another kind of polymer semiconductors with different charge transporting mechanism. Here we report the first near‐amorphous n‐type conjugated polymer with decent electron mobility, which features a remarkably rigid, straight and planar polymer backbone. The molecular design strategy is to copolymerize two fused‐ring building blocks which are both electron‐accepting, centrosymmetrical and planar. The polymer is the alternating copolymer of double B←N bridged bipyridine (BNBP) unit and benzobisthiazole (BBTz) unit. It shows a decent electron mobility of 0.34 cm 2 V −1 s −1 in organic field‐effect transistors. The excellent electron transporting property of the polymer is possibly due to the ultrahigh backbone stiffness, small π‐π stacking distance, and high molecular weight. Abstract : Amorphous conjugated polymers represent another kind of polymer semiconductor with a different charge transporting mechanism. An n‐type conjugated polymer with rigid, straight and planar backbone has now been designed and synthesized. It is amorphous in a thin film but exhibits an electron mobility of 0.34 cm 2 V −1 s −1 .